Chitosan selectively promotes adhesion of myoblasts over fibroblasts. Issue 6 (6th January 2014) - Iyer, Shama R.; Udpa, Natasha; Gao, Yingxin
Abstract Treatment of ventral hernias frequently makes use of synthetic and biological meshes, often resulting in scar tissue formation and incomplete muscle regeneration. Chitosan has been shown to promote a regenerative response than a fibrotic response. The objective of this study is to determine the effects of chitosan on myoblast and fibroblast adhesion and the underlying mechanisms. Primary myoblast cells, embryonic fibroblasts, and 1:1 coculture of both cell types were seeded on chitosan‐coated and uncoated tissue culture plates. The number of attached cells was measured at 5, 24, 48, and 72 h after seeding. At 5 h after seeding, expression and structural organization of actin, integrin β3, and integrin β1 were analyzed. With chitosan, primary fibroblasts had 2.7 times smaller F‐actin fraction, and more primary myoblasts with higher expression of integrin β3 were seen. Moreover, a higher ratio of myoblasts to fibroblasts was seen with chitosan, with a ratio higher than one at 48 and 72 h after seeding and greater than a twofold increase in ratio when compared with uncoated plates. A higher organization of actin and integrin β3 network around nucleus of myoblasts was observed with chitosan, whereas reorganization in actin and integrin β1 network was observed in fibroblasts. In conclusion, chitosan promotes myoblast adhesion with higher expression of integrin β3 and inhibits fibroblast adhesion with reorganization of actin and integrin β1 network. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1899–1906, 2015.